Edukasi Literasi Digital untuk Pencegahan Penyebaran Berita Hoaks pada Siswa SMP Swasta Advent Medan - Lismardiana Sembiring; Jaidup Banjarnahor; Harlen Silalahi; Dumariani Silalahi; Jenheri Rejeki Tarigan; Erni Dewi Munthe; Supelio (Universitas Methodist Indonesia, 2026)
The increasing use of smartphones to access social media among junior high school students can lead to conflict and loss of private data. The purpose of this digital literacy education is to provide and strengthen understanding of digital literacy education in social media. The method used is a qualitative descriptive approach, starting with the problem formulation stage, data collection stage, data analysis stage, and reporting stage. The data analysis results indicate that 100% of junior high school students use smartphones 4-6 hours per day, and 57% use more than 6 hours per day. Furthermore, an average of 100% have social media accounts, namely Instagram and Threads (33%). This demonstrates the need for junior high school students to be equipped with an understanding of digital literacy to improve critical thinking skills, protect them from cybercrime, and be able to analyze and verify the accuracy of news, thereby creating digital ethics in cyberspace and reducing the risk of conflict.